The Effect of Symmetrical Involvement of the Knee Joints in Moderate Osteoarthritis on Individuals' Report of Pain and Function (Part One of a Preliminary Study): Intermittent and Constant Osteoarthritis Pain Measure - Behrooz Melyanian; Zeinab Niki; Zahra Sadat Rezaeian (Vesnu Publications, 2016)
Introduction: Knee osteoarthritis is the most common type of arthritis and results in functional impairment because of pain and articular tissue degeneration. The present study compared the reports of pain among subjects with symmetric and asymmetric moderate knee osteoarthritis using the Intermittent and Constant Osteoarthritis Pain (ICOAP) measure. Materials and Methods: The 20 subjects with moderate knee osteoarthritis were purposefully assigned to symmetric and asymmetric knee groups. After obtaining informed consent forms form the subjects, demographic information was collected they completed the Persian version of the ICOAP measure. Subjects' responses to each item, score in each section, and total scores were compared between the two groups. The results were analyzed using Mann-Whitney U test. Results: There was no significant difference between the groups in terms of constant and intermittent pain scores and total score (P < 0.05). Nonetheless, the comparison of each item showed that constant (P = 0.04) and intermittent pain (pain that comes and goes) (P = 0.02) had greater negative impact on sleep in the asymmetric group. In addition, more severe intermittent pain (P = 0.04) was reported in the asymmetric group. Conclusion: It seems that despite the lack of any significant difference between the types of pain resulting from knee osteoarthritis, the subjects' complaints of pain intensity and its impact on sleep quality differ.